The Road to Negative Behavior: Discriminatory Intentions in the German Population - Asbrock, Frank; Christ, Oliver; Wagner, Ulrich (International Journal of Conflict and Violence (IJCV), 2007)
This study analyzes discriminatory intentions shared by members of the German majority against several outgroups in Germany. Patterns of discriminatory intentions against various minority groups were investigated for several indicators, including gender, age, and political orientation, by means of a representative survey (N = 1,778). The relationship between prejudices and discriminatory intentions against different target groups was also analyzed. Prejudice and discriminatory intentions show moderate but consistently positive correlations in relation to one and the same target group. Moreover, it was found that discriminatory intentions against one outgroup are related to hostile attitudes towards other outgroups, too. The results support the hypothesis of a syndrome of group-focused enmity.